2002
DOI: 10.1007/s001980200083
|View full text |Cite
|
Sign up to set email alerts
|

Uneven Deficits in Vertebral Bone Density in Postmenopausal Patients with Primary Hyperparathyroidism as Evaluated by Posterior–Anterior and Lateral Dual-Energy Absorptiometry

Abstract: This investigation was undertaken to determine whether the preservation of bone mass in patients with mild primary hyperparathyroidism (PHPT) could be detected when measuring spine density in the lateral projection. We compared the bone mineral density (BMD) of L2-L4 utilizing the posterior-anterior (PA) and lateral projections in postmenopausal patients with PHPT and in a group of 27 postmenopausal normal women. Thirty-three consecutive postmenopausal patients with PHPT were studied; 25 were asymptomatic wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…In fact, according to 2002 guidelines, skeletal involvement in M PHPT patients is only evaluated by BMD measurement. As expected, in patients with more severe disease, BMD values were significantly lower at any site compared with both M patients and C. However, confirming our previous results (22), in M patients BMD values at the LS were significantly higher than C, supporting the hypothesis of an anabolic action of PTH on cancellous bone in postmenopausal women with mild disease. To define this action better, we also calculated volumetric BMD of the third lumbar vertebra according to an accepted and widely used method (19).…”
Section: Healthy Women (C)supporting
confidence: 89%
“…In fact, according to 2002 guidelines, skeletal involvement in M PHPT patients is only evaluated by BMD measurement. As expected, in patients with more severe disease, BMD values were significantly lower at any site compared with both M patients and C. However, confirming our previous results (22), in M patients BMD values at the LS were significantly higher than C, supporting the hypothesis of an anabolic action of PTH on cancellous bone in postmenopausal women with mild disease. To define this action better, we also calculated volumetric BMD of the third lumbar vertebra according to an accepted and widely used method (19).…”
Section: Healthy Women (C)supporting
confidence: 89%
“…In the spine, reduction was found in some (28,34,37) but not all (35,36,38) studies, and similarly for the hip, both aBMD reductions (36,37) and no difference (34) have been reported. The aBMD findings in our study are in accordance with those previously described, but we did observed reductions in aBMD at all three skeletal sites.…”
Section: Discussionmentioning
confidence: 89%
“…Several reports suggest that these noncharacteristic phenomena of pHPT are also present in asymptomatic as well as in normocalcemic diseases [5, 7, 8]. Whilst low bone mineral density (BMD) is a traditional manifestation of pHPT [9, 10], studies of the characteristic presentation in mild pHPT are contradictory [11, 12]. In addition, population‐based analyses of BMD in mild and asymptomatic pHPT have not been presented.…”
Section: Introductionmentioning
confidence: 99%